Heterogeneity in head and neck cancer incidence among black populations from Africa, the Caribbean and the USA: Analysis of cancer registry data by the AC3. (December 2021) - Auguste, Aviane; Gathere, Samuel; Pinheiro, Paulo S.; Adebamowo, Clement; Akintola, Adeola; Alleyne-Mike, Kellie; Anderson, Simon G.; Ashing, Kimlin; Awittor, Fred Kwame; Awuah, Baffour; Bhakkan, Bernard; Deloumeaux, Jacqueline; et al.
Abstract: Background: Africa and the Caribbean are projected to have greater increases in Head and neck cancer (HNC) burden in comparison to North America and Europe. The knowledge needed to reinforce prevention in these populations is limited. We compared for the first time, incidence rates of HNC in black populations from African, the Caribbean and USA. Methods: Annual age-standardized incidence rates (IR) and 95% confidence intervals (95%CI) per 100, 000 were calculated for 2013–2015 using population-based cancer registry data for 14, 911 HNC cases from the Caribbean (Barbados, Guadeloupe, Trinidad & Tobago, N = 443), Africa (Kenya, Nigeria, N = 772) and the United States (SEER, Florida, N = 13, 696). We compared rates by sub-sites and sex among countries using data from registries with high quality and completeness. Results: In 2013–2015, compared to other countries, HNC incidence was highest among SEER states (IR: 18.2, 95%CI = 17.6–18.8) among men, and highest in Kenya (IR: 7.5, 95%CI = 6.3–8.7) among women. Nasopharyngeal cancer IR was higher in Kenya for men (IR: 3.1, 95%CI = 2.5–3.7) and women (IR: 1.5, 95%CI = 1.0–1.9). Female oral cavity cancer was also notably higher in Kenya (IR = 3.9, 95%CI = 3.0–4.9). Blacks from SEER states had higher incidence of laryngeal cancer (IR: 5.5, 95%CI = 5.2–5.8) compared to other countries and even Florida blacks (IR: 4.4, 95%CI = 3.9–5.0). Conclusion: We found heterogeneity in IRs for HNC among these diverse black populations; notably, Kenya which had distinctively higher incidence of nasopharyngeal and female oral cavity cancer. Targeted etiological investigations are warranted considering the low consumption of tobacco and alcohol among Kenyan women. Overall, our findings suggest that behavioral and environmental factors are more important determinants of HNC than race. Graphical Abstract: ga1 Highlights: First comparison of HN Cancer incidence between blacks from USA, Caribbean and Africa. USA and Guadeloupe males had the highest incidence rates. Incidence of female oral cavity cancer is high in Kenya. The sex ratio for HN cancer was smaller for Africa than the Caribbean and the USA.